After the truth commission: gender and citizenship in Timor-Leste - Kent, Lia (Human rights review, 2016)
This article explores the relationship between truth commissions and gendered citizenship through a case study of Timor-Leste. It examines how, 10 years after the Commission for Reception, Truth and Reconciliation (CAVR) has completed its work, women’s citizenship remains constrained by, and negotiated within, deeply gendered narratives of nation-building that are informed by historical experiences of the resistance struggle. The power of these narratives—which foreground heroism rather than victimisation—underscores the need to situate truth commissions as part of an ongoing politics of memory. Despite the power of political elites to shape this politics, the continued marginalisation of sections of society within official narratives is also providing an impetus for alternative truth-telling efforts that seek to broaden public perspectives on the past. By promoting new narratives of women’s experiences of the conflict, these projects might be understood as attempts to negotiate and transform gendered conceptions of citizenship in the present and for the future.